Effective Strategy Implementation Conceptualizing Firms$1 (BStrategy Implementation Capabilities and Assessing Their Impact on Firm Performance /s - Huber, Adele J.; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
Adele J. Huber discovers that a firm$1 (Bs strategy implementation capabilities are a key driver of the strategies' performance outcomes. Drawing on organizational learning theory, she identifies the organizational abilities and processes that constitute a firm's Strategy Implementation Capability construct and shows empirically that the concept is very valuable in explaining how innovative strategies translate into a firm's performance. Her findings are particularly interesting for managers and researchers who focus on strategy formulation and execution. They also show the relation between strategy implementation and competitive advantage.s
Keywords: Economics; Industrial management; Economics/Management Science; Management/Business for Professionals